2022
DOI: 10.1097/inf.0000000000003518
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gestational COVID-19 on Neonatal Outcomes

Abstract: Background: The vertical transmission of severe acute respiratory coronavirus-2 (SARS-CoV-2) remains highly debated. Here, we evaluated SARS-CoV-2-transmission in newborns with intrauterine conditions. Methods: This was a prospective, observational and multicentric study involving 13 Spanish hospitals included in the GEStational and NEOnatal-COVID cohort. Pregnant women with microbiologically confirmed SARS-CoV-2 infection during any trimester of pregnancy or delivery and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
4
13
0
Order By: Relevance
“…However, SARS-CoV-2 can invade placental tissue and cause infection and inflammation in placental cells [35] . A prospective, multicenter investigation found that infection occurred in 5.1 % of newborns born to mothers infected with SARS-CoV-2 during pregnancy, implying that SARS-CoV-2 can be transmitted intrauterine [36] . Strong evidence from another study revealed that 12 % of SARS-CoV-2-positive pregnant women transmit the virus intrauterine, and that intrauterine transmission may even occur in asymptomatic individuals [37] .…”
Section: Discussionmentioning
confidence: 99%
“…However, SARS-CoV-2 can invade placental tissue and cause infection and inflammation in placental cells [35] . A prospective, multicenter investigation found that infection occurred in 5.1 % of newborns born to mothers infected with SARS-CoV-2 during pregnancy, implying that SARS-CoV-2 can be transmitted intrauterine [36] . Strong evidence from another study revealed that 12 % of SARS-CoV-2-positive pregnant women transmit the virus intrauterine, and that intrauterine transmission may even occur in asymptomatic individuals [37] .…”
Section: Discussionmentioning
confidence: 99%
“…The probability of viral vertical and perinatal transmission is still controversial. Some studies support that transmission of SARS-CoV2 during pregnancy is extremely low (18)(19)(20) while other published series have reported several cases of CoVid-19 infected newborns (21)(22)(23)(24). Nevertheless, it has been observed that a potent antibody response (IgM, IgG and IgA, especially) occurs in the serum and milk of mothers infected with SARS-CoV2 during pregnancy that can be transferred to the foetus before and after the birth.…”
Section: Introductionmentioning
confidence: 95%
“…In keeping with the published rates of mother to infant transmission (5), we found just under 2% of babies born to women positive for SARS-CoV-2 at birth also had a positive test at some point in the neonatal period. Not all babies of infected women were tested at birth (see below), and it is possible that rates may have been higher if all were screened (10).…”
Section: Discussionmentioning
confidence: 99%